Docking And Molecular Dynamics Simulation Studies Of Insulin-P- Cyclodextrin Interactions - Muhammad, Erma Fatiha (2016)
Protein-ligand interactions play an essential role in the design of new pharmaceutical products. This study attempts to understand the theoretical basis on the structure and dynamics of insulin-cyclodextrin complex for new oral insulin formulation. Docking and molecular dynamics simulations explore the interactions between insulin monomer and insulin dimer with 0- cyclodextrins (0-CDs). A multiple molecular docking study was performed using the Autodock v4.2 program to determine the number of 0-CD that can adhere to the binding sites of insulin as well as to determine the most stable conformations of insulin to p-CDs. A 100 random structure docking using 1:1 insulin monomer-P-CD and insulin dimer-p-CD ratio were conducted and from the final docked structure, additional 0-CDs were added and the process were repeated until the energy increase. Molecular docking results revealed that a maximum of four 0-CDs can bind to an insulin structure with the 1:3 insulin-P-CD ratios having the lowest binding free energy. A 100 ns molecular dynamics simulation was then conducted to verify the results obtained by molecular docking.